Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $(E,g)$ be a real oriented inner product space with orthonormal basis $(e_1, \dots, e_n)$ with corresponding dual basis $(e^1, \dots, e^n)$. Then, for any $\beta \in \Lambda^0(V) := \mathbb{R}$, how does one prove that $$ * \beta = \beta \omega_E $$ where $\omega_E := e^1 \wedge \cdots \wedge e^n$ denotes the induced volume form for $(V,g)$?

I welcome feedback about the correctness of my approach and any alternate approaches that might be more efficient.

share|cite|improve this question

First, note that $1 \in \Lambda^0(E)$ is the only positively-oriented orthonormal basis for $\Lambda^0(E)$. For, suppose that a nonzero scalar $k$ is basis which we can do since $\Lambda^0(E)$ is one-dimensional. Then if $k$ is orthonormal with respect to $g$, $$ g(k, k) = 1 \implies |k|^2 = 1 \implies k = \pm 1 $$ But, since we require positive orientation this reduces to $k = 1$. So, without loss of generality, we take $1$ as a basis for $\Lambda^0(E)$. Also, to be clear, the $g$ referenced here is inner product on $\Lambda^k(E)$, $k=1, \dots, n$, that is induced by the inner product on $(V, g)$. Perhaps a better notation would be $g_0$.

In any event, the Hodge-$*$ is the unique isomorphism $* \colon \Lambda^0(E) \rightarrow \Lambda^n(E)$ such that $$ \alpha \wedge (* \beta) = g(\alpha, \beta)\omega_{E} $$ for all $\alpha \in \Lambda^0(E)$. If follows then from the bilinearity and orthonormality of $g$ that \begin{align*} \alpha \wedge (* \beta) &= g(\alpha, \beta)\omega_{E}\\ &= g(\alpha \cdot 1, \beta \cdot 1) \omega_{E}\\ &= \alpha \beta g(1,1) \omega_{E}\\ &= \alpha \beta \omega_{E}. \end{align*} But $\alpha$ is just a scalar so $$ \alpha \wedge (*\beta) = \alpha \cdot (* \beta) $$ and consequently $$ \alpha \cdot (* \beta) = \alpha \beta \omega_E \implies * \beta = \beta \omega_E. $$

share|cite|improve this answer
That's correct. The last step is unnecessary: you have already shown that $\alpha\wedge (\beta \omega_E)=g(\alpha,\beta)\omega_E$, so by the characterization/definition you conclude $\beta \omega_E=\star(\beta)$. – wildildildlife Jul 8 '12 at 20:26

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.